Microstructure, mechanical and thermal characteristics of foamed geopolymer concrete using fly ash and palm oil fuel ash as binders / Michael Liu Yong Jing - Michael Liu, Yong Jing (2014)
The use of cement is still needed within the manufacture of concrete even though the current concrete are of composite materials. This phenomenon has led to the huge release of carbon dioxide (CO2) into the atmosphere and initiated the global warming. Other than the manufacturing sector, the energy sector such as power plants generate large amount of noxious gases as well. The enhancement of energy efficacy of buildings could be achieved by reducing the heat loss in buildings that would lessen the amount of energy used and thus, scale down the consumption of fossil fuels by power plants. In addition, the cumulative agricultural wastes (i.e. oil palm shell (OPS), empty fruit bunches, palm oil fuel ash (POFA), and palm oil clinker) in Malaysia has become a significant factor towards the land and air pollutions especially in the proximity of the palm oil factories, which led to the disorder in environmental sustainability. A more resource- and energy-efficient construction industry would preserve the environment. In this research work, the geopolymer technology is introduced in the production of concrete to omit the use of cement, which also utilized the OPS as lightweight coarse aggregate and the binders consist of POFA and fly ash (FA). Additionally, foam is added to enhance the thermal insulation characteristic. The concrete termed as oil palm shell foamed geopolymer concrete (OPSFGC). Thus far, there is no literature available on this type of concrete. The objective of this research was to explore the possibility of the OPSFGC as structural and insulating material. Hence, this research investigated the physical properties of the OPS, mechanical and transport properties and thermal behaviour of the OPSFGC. The in-depth study on the microstructure of OPSFGC and its paste were analysed as well. Three OPSFGC mixtures with target densities of 1300, 1500 and 1700 kg/m3 were prepared using artificial foaming agent; a control mix without foam (OPSNFGC) and conventional materials – block and brick – were used for comparison. It is found that OPSFGC and OPSNFGC are characterized as lightweight concrete (LWC). The mechanical properties of OPSFGC and OPSNFGC, such as compressive, splitting tensile and flexural strengths, generally reduced with the reduction in the density; the modulus of elasticity (MOE) also followed a similar trend. Moreover, a high early strength (3-day compressive strength) can be achieved of up to 90% when compared with the 28-day compressive strength, however, rate of strength gain was only about 11.3% after 7-day. Furthermore, the OPSFGC17 and OPSNFGC exhibited ‘fair’ quality concrete with UPV values of more than 3 km/s. In accordance with RILEM (1983), OPSFGC13 and OPSFGC15 can be categorized as structural and insulating concrete – Class-II with strength and thermal conductivity of 8 and 13 MPa, and 0.47 and 0.50 W/mK, correspondingly. Whilst the OPSFGC17 and OPSNFGC produced a higher compressive strength of about 26 and 30 MPa, respectively fall under the structural grade LWC. Last but not least, the microstructure analysis showed the morphology and mineralogy of the specimens, which validated the obtained results and discussion.